2019
DOI: 10.1111/cmi.13087
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulatory roles of PtdIns(4,5)P2generating enzyme EhPIPKI in actin dynamics and phagocytosis ofEntamoeba histolytica

Abstract: Motility and phagocytosis are the two important processes that are intricately linked to survival and virulence potential of the protist parasite Entamoeba histolytica. These processes primarily rely on actin-dependent pathways, and regulation of these pathways is critical for understanding the pathology of E. histolytica. Generally, phosphoinositides dynamics have not been explored in amoebic actin dynamics and particularly during phagocytosis in E. histolytica. We have explored the roles of PtdIns(4,5)P 2 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Such isotype-specific and tempo-spatial recruitment of EhLTP1 and EhLTP3 was similar to that of AGC kinases 2 and 1, respectively [19], which may infer potential cross talk between the proteins via PIPs. The localization of EhLTP1 and EhLTP3, shown in this study, is similar with that of PtdIns(4,5)P 2 and their synthetic enzyme, EhPIPKI [20,38]. This is consistent with the fact that both EhLTP1 and 3 have PtdIns4P and PtdIns(4,5)P 2 transport activities.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Such isotype-specific and tempo-spatial recruitment of EhLTP1 and EhLTP3 was similar to that of AGC kinases 2 and 1, respectively [19], which may infer potential cross talk between the proteins via PIPs. The localization of EhLTP1 and EhLTP3, shown in this study, is similar with that of PtdIns(4,5)P 2 and their synthetic enzyme, EhPIPKI [20,38]. This is consistent with the fact that both EhLTP1 and 3 have PtdIns4P and PtdIns(4,5)P 2 transport activities.…”
Section: Discussionsupporting
confidence: 89%
“…PtdIns4P and PtdIns(4,5)P 2 )] to EhPIPKI and PtdIns 3-kinase, respectively (S9 Fig), as suggested as a role of LTPs in lipid metabolism [2]. The localization and dynamics of PIs including PtdIns4P [20,39], PtdIns3P [35], PtdIns(4,5)P 2 [38], PtdIns (3,4,5)P 3 [19,37] in E. histolytica during trogo-and phagocytosis were well studied through their binding effectors. It has been shown that EhFP4 interacts with PtdIns4P, EhSNX1 and 2 interact with PtdIns3P, and EhAGCK1 and 2 interact with PtdIns(3,4,5)P 3 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Calcium (Ca 2+ ) has evolved as one of the key second messengers in this pathogen regulating phagocytosis at multiple levels. The pathogen encodes several novel Ca 2+ binding proteins (CaBPs), PIP 2 , IP 3 , IP 4 , and P-type Ca 2+ -ATPases, for Ca 2+ regulation and homeostasis (Sahoo et al, 2004;Loftus et al, 2005;Jain et al, 2008;Nozaki and Bhattacharya, 2014;Sharma et al, 2019). The calcium binding protein 1 (EhCABP1) has been identified as the central indispensable molecule recruited at the early phagocytic cups.…”
Section: Introductionmentioning
confidence: 99%
“…The kinase EhAK1 along with other cytoskeletal proteins such as actin branching complex Arp 2/3, Myosin1B, and the calcium binding protein 3 (EhCABP3) are known to regulate the formation and progression of the phagocytic cup toward its closure (Aslam et al, 2012;Babuta et al, 2018). CaBPs (EhCaBP1, EhCaBP3, and EhCaBP5) have been shown to play a crucial role in establishment of phagocytosis in E. histolytica (Sahoo et al, 2004;Jain et al, 2008;Aslam et al, 2012;Kumar et al, 2014b;Nozaki and Bhattacharya, 2014;Sharma et al, 2019). However, relative to Ca 2+ signaling, the knowledge of another crucial second messenger cAMP and its signaling pathway is very limited in E. histolytica.…”
Section: Introductionmentioning
confidence: 99%